摩托车V型皮带式无级变速器的力学分析 - 任大鹏; 秦伟 (Jixie chuandong)
The operation principle of V-belt continuously variable transmissions equipped on motorcycles is presented. On the basis of force analysis of the centrifugal roller, the driving clutch and the driven clutch, the relation between the axial displacement of driving clutch and that of the driven clutch is proposed. The conclusions obtained can be directly applied to the analysis and design of V-belt type CVT on motorcycles.